SYSTEMATIC REVIEW: THE RELATIONSHIP BETWEEN MOTHER'S AGE AND HYPERTENSION IN PREGNANCY - Yanata, Tsana Vania; Lestari Sudaryanti (UNIVERSITAS AIRLANGGA, 2025)
Background: The high maternal mortality rate is caused by a high risk of pregnancy. High risk is a condition that can endanger the mother and fetus and is associated with pregnancy, childbirth and the puerperium. 90% of maternal deaths are caused by obstetric risk complications and increasing 15% in mothers who have risk factors. Hypertension in pregnancy is a high risk for pregnant women and can be caused by several risk factors. Several risk factors of hypertension in pregnancy are age, history of hypertension, family support, and stress levels. The purpose of this study was to determine the relationship between maternal age and the incidence of hypertension in pregnancy. Method: This research is a systematic review with inclusion criteria are Indonesian journal from 2020 – 2022, full article, and open access. Researchers will exclude any other journal not in Indonesian or English, not an open acces article and not a research study of mother’s age and hypertension in pregnancy. This research is a literature study using descriptive method and conducting journal searches on several scientific websites with keywords relationship, factors, age, and hypertension in pregnancy. Results: Based on a literature study of the 5 journals found, it was found most of the mothers are at risk of experiencing hypertension in pregnancy. Age at risk is more susceptible to experiencing hypertension in pregnancy, it is caused by the development of reproductive organs that are not optimal enough in mothers who are too young and degenerative processes in old mothers. Conclusion: Age at risk or < 20 years and > 35 years has a significant relationship with hypertension in pregnancy.